Dynamic programming for optimal operation of a biofuel micro CHP-HES system. (15th December 2017) - Chen, X.P.; Hewitt, N.; Li, Z.T.; Wu, Q.M.; Yuan, Xufeng; Roskilly, Tony
Highlights: The dynamic programming optimisation is applied to a biofuel micro CHP-HES system. A decision tree method is proposed to solve multi-dimension dynamic programming problem. The system efficiency is improved by 26.7% with the proposed strategy. System dynamic is improved due to fast response of batteries and supercapacitors. Abstract: Combined heat and power systems (CHPs) have received much attention in recent years due to increasing use of bio-fuels and distributed generation (DG). Conventionally, they are connected to the power grid to balance electrical demands and supplies. This research investigated an off-grid (stand-alone) biofuel micro CHP system with hybrid energy storage (HES) (including battery banks and super-capacitors) by developing an energy management strategy based on dynamic programming (DP). DP is an optimization strategy which has been applied to energy systems in recent years. However, they suffer from dimension problems when the number of variables increases. This work is the first attempt to apply the decision tree (DT) to multi-dimension DP solutions in energy systems. The energy efficiency is improved from 45.77% to 57.97% using diesel-biofuels and the system has a potential for commercial applications. The experimental test results validate its feasibility and effectiveness.